2018
DOI: 10.1002/anie.201805640
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐Directed Intracellular Self‐Assembly of Chiral Nanorod Dimers

Abstract: MicroRNAs (miRNAs), a kind of single-stranded small RNA molecules, play a crucial role in physiological and pathological processes in human beings. We describe here the detection of miRNA, by side-by-side self-assembly of plasmonic nanorod dimers in living cells, which gives rise to a distinct intense chiroplasmonic response and surface-enhanced Raman scattering (SERS). The dynamic assembly of chiral nanorods was confirmed by fluorescence resonance energy transfer (FRET), also in living cells. Our study provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
126
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 40 publications
0
126
0
1
Order By: Relevance
“…The assay provides an LOD of 100 pM for the RNA. A similar assay was applied for the detection of miRNA (e.g., microRNA‐21, overexpressed in most tumors marker) in living cells using DNA–Au nanorods . In presence of the miRNA, two Au nanorods with different DNA strands complementary with miRNA form a dimer, leading to increased CD signals at 815 and 657 nm and enhancement of the surface‐enhanced Raman scattering (SERS).…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…The assay provides an LOD of 100 pM for the RNA. A similar assay was applied for the detection of miRNA (e.g., microRNA‐21, overexpressed in most tumors marker) in living cells using DNA–Au nanorods . In presence of the miRNA, two Au nanorods with different DNA strands complementary with miRNA form a dimer, leading to increased CD signals at 815 and 657 nm and enhancement of the surface‐enhanced Raman scattering (SERS).…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…The complementarity of specific functional groups in these biomolecules has been extensively used for the design and synthesis of a wide range of chiral nanoarchitectures that display circular dichroism (CD) signals at the LSPR wavelengths. This research has in turn generated a wide range of applications for chiral plasmons in the fields of chiral biodetection, enantioselective sensing, and catalysis . The basic principle behind most of these applications involves tuning chiral LSPR by varying the size and shape of the particles, through the controlled assembly of nanoparticles, by changing the interparticle distance, or by altering the dielectric constant of the surrounding medium.…”
Section: Introductionmentioning
confidence: 99%
“…In this study,w ec reated am ultifunctional integrated theranostic nanoplatform, in which copper (II) phthalocyanine (CuPc) molecule played double key roles in PDT as well as in situ SERS monitoring and imaging capability.O no ne hand, hexagonal boron nitride nanosheets (h-BNNS) were developed for improving the SERS signals of CuPc with high enhanced factor (EF) value.CuPc was first used as asensitive and accurate diagnostic sounder for miR-21, which was chosen as target miRNAf or its significant elevated content in av ariety of cancers as reported previously,e specially in breast cancer (BC). [7] Thec ircle amplification strategy was specifically designed by hairpin G-quadruplex (HG) DNAfor further enhancing the detection sensitivity.T he ratiometric determination was designed with built-in corrections for avoiding environmental effects.I nt his way,t he developed nanoplatform with ultrasensitivity,h igh selectivity,a nd accuracy was employed for miR-21 monitoring and imaging with limit of detection (LOD) down to 0.7 fm in live cells,w hich was 100 times lower than that of the previous methods. [8,9] On the other hand, CuPc intercalated into HG DNAimproved its solubility to act as an effective PS for PDT.H ere,r eal-time monitoring of miR-21 with the developed theranostic nanoplatform guided the early theranostics to improve the therapeutic efficiency of BC.I nt he early stage of the tumor, corresponding to miR-21 concentration of lower than 7f m, [10] low doses (25 mgmL À1 )o fd rug (CuPc@HG@BN) completely eliminated the tumor only for 3days.B oth in vitro and in vivo data demonstrated that the integrated nanoplatform showed remarkable enhancement in PDT efficiencyw ith minimized damage to normal tissues.…”
mentioning
confidence: 99%